2020
DOI: 10.1038/s41396-020-00828-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic versatility of the nitrite-oxidizing bacterium Nitrospira marina and its proteomic response to oxygen-limited conditions

Abstract: The genus Nitrospira is the most widespread group of nitrite-oxidizing bacteria and thrives in diverse natural and engineered ecosystems. Nitrospira marina Nb-295T was isolated from the ocean over 30 years ago; however, its genome has not yet been analyzed. Here, we investigated the metabolic potential of N. marina based on its complete genome sequence and performed physiological experiments to test genome-derived hypotheses. Our data confirm that N. marina benefits from additions of undefined organic carbon s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 104 publications
(168 reference statements)
5
66
0
Order By: Relevance
“…It has been demonstrated that several Nitrospira species can use formate as an energy source and that their genomes contain a formate transporter (FocA) and a soluble NAD + -reducing formate dehydrogenase (FDH), which catalyzes the oxidation of formate to CO 2 with concomitant reduction of NAD + to NADH ( 5 , 9 ). Notably, N. moscoviensis and the marine Nitrospira marina were reported to grow less efficiently on formate than on nitrite ( 5 , 9 ), a trend we confirmed for N. moscoviensis in batch experiments (see Fig. S4A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that several Nitrospira species can use formate as an energy source and that their genomes contain a formate transporter (FocA) and a soluble NAD + -reducing formate dehydrogenase (FDH), which catalyzes the oxidation of formate to CO 2 with concomitant reduction of NAD + to NADH ( 5 , 9 ). Notably, N. moscoviensis and the marine Nitrospira marina were reported to grow less efficiently on formate than on nitrite ( 5 , 9 ), a trend we confirmed for N. moscoviensis in batch experiments (see Fig. S4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, N. marina also showed poor growth with formate compared to that with nitrite ( 9 ), even though it possesses a cytoplasmic formate dehydrogenase that is only distantly related to the one of N. moscoviensis . Therefore, it is tempting to speculate that poor growth on formate might be a general feature of Nitrospira caused by its overall metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrospira species are well known to be metabolically versatile, with a wide range of functional potentials, including nitrite oxidation, hydrogen oxidation, urea conversion, formate oxidation, nitrate reduction, and complete ammonium oxidation ( 24 , 37 , 38 , 52 , 58 ). This metabolic diversity likely creates opportunities for functionally degenerate Nitrospira populations to coexist within a bioreactor by differentiating in niche space through auxiliary metabolic specializations while also sharing a niche space of nitrite oxidation ( 34 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings therefore reveal that physiological diversity at the lineage level, and possibly at the sub-lineage or strain level, within Nitrospira-dominated communities can facilitate niche-partitioning and acclimation to FA-exposure as a press-disturbance when applied as an engineering control strategy to promote low-energy nitrogen removal. Nitrospira species are well-known to be metabolically versatile, with a wide range of functional potentials including nitrite oxidation, hydrogen oxidation, urea conversion, formate oxidation, nitrate reduction, and complete ammonium oxidation (24,37,38,52,60). This metabolic diversity likely creates opportunities for functionally degenerate Nitrospira populations to co-exist within a bioreactor by differentiating in niche space through auxiliary metabolic specializations, while also sharing a common niche space of nitrite oxidation (34,61).…”
Section: Discussionmentioning
confidence: 99%